Anti-theft device staining on banknotes detected by mass spectrometry imaging. (March 2016) - Correa, Deleon Nascimento; Zacca, Jorge Jardim; Rocha, Werickson Fortunato de Carvalho; Borges, Rodrigo; de Souza, Wanderley; Augusti, Rodinei; Eberlin, Marcos Nogueira; Vendramini, Pedro Henrique
Graphical abstract: Highlights: ATM theft, particularly with the use of explosives, is a serious and increasing crime in Brazil. Anti-theft device (ATD) ink makes banknotes worthless and nontransferable after an ATM blown up. Rhodamine family and 1-methylaminoanthraquinone (MAAQ) are the dyes applied in the world as ATD. Mass spectrometry imaging (MSI) allows tracking painted banknotes after the clean and bleach attempt. Abstract: We describe the identification and limits of detection of ink staining by mass spectrometry imaging (MSI), as used in anti-theft devices (ATDs). Such ink staining is applied to banknotes during automated teller machine (ATM) explosions. Desorption electrospray ionization (DESI) coupled with high-resolution and high-accuracy orbitrap mass spectrometry (MS) and a moving stage device were applied to obtain 2D molecular images of the major dyes used for staining, that is, 1-methylaminoanthraquinone (MAAQ), rhodamine B (RB) and rhodamine 6G (R6G). MAAQ could not be detected because of its inefficient desorption by DESI from the banknote cellulose surface. By contrast, ATD staining on banknotes is perceptible by the human naked eye only at concentrations higher than 0.2 μg cm −2, whereas both RB and R6G at concentrations 200 times lower (as low as 0.001 μg cm −2 ) could be easily detected and imaged by DESI–MSI, with selective and specific identification of each analyte and their spatial distribution on samples from suspects. This technique is non-destructive, and no sample preparation is required, which ensures sample preservation for further forensic investigations.